1995
DOI: 10.1007/bf00017102
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elevated [CO2] on plant-soil carbon below-ground: A summary and synthesis

Abstract: We undertake a synthesis of the most relevant results from the presentations at the meeting "Plant-Soil Carbon Below-Ground: The Effects of Elevated CO2" (Oxford-UK, September 1995), many of which are published in this Special Issue. Below-ground responses to elevated [CO2] are important because the capacity of soils for long-term carbon sequestration. We draw the following conclusions: (i) several ecosystems exposed to elevated [CO2] showed sustained increased CO2 uptake at the plot level for many years. A fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 47 publications
4
84
0
1
Order By: Relevance
“…In natural systems, finite resource availability might constrain the long-term flux of C into plant and soil systems, but for agricultural systems in which nutrients and water are often less growth-limiting, constraints will be less stringent (Berntson & Bazzaz, 1996 ;Canadell et al, 1996).…”
Section: Carbon Allocation Below Groundmentioning
confidence: 99%
See 4 more Smart Citations
“…In natural systems, finite resource availability might constrain the long-term flux of C into plant and soil systems, but for agricultural systems in which nutrients and water are often less growth-limiting, constraints will be less stringent (Berntson & Bazzaz, 1996 ;Canadell et al, 1996).…”
Section: Carbon Allocation Below Groundmentioning
confidence: 99%
“…For several crop species, up to 40% of net C fixed is allocated below ground (Gorissen, 1996 ;Gregory et al, 1996), and the proportion of total plant photosynthate allocated to roots tends to increase in plants growing in elevated [CO # ] (Canadell et al, 1996). For example, Rattray et al (1995) reported that the proportion of "%C translocated below ground almost doubled, from 18% at ambient [CO # ] to 34% under elevated [CO # ].…”
Section: Carbon Allocation Below Groundmentioning
confidence: 99%
See 3 more Smart Citations